STRUCTURAL STEEL ANALYSIS DESIGN OF COMMERCIAL FACTORIES FOR LOADING AND EARTHQUAKE RESISTANCE - Sami N O Bakarman (Neutron, 2019)
In the university my courses According to the widely used of "Steel buildings " in these days which taught us to analyze and design this flooring system that can achieve the requirements of this structure. Also use several programs like (ETAB, SAP , ROBOT & TEKLA etc), beside that I used different combinations for earthquake resistance. It analysis and design according to the eurocode AISC 14.0 , in addition to that I used the program of Autodesk Robot Structural, AUTO CAD 2013 & Tekla Structure. while I have many components I used that program to help me for designing, by include the loads as input, then I got different diagrams and diameters for each part.